2016
DOI: 10.1530/erc-16-0299
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CDK9: a promising therapeutic opportunity in prostate cancer

Abstract: Cyclin-dependent kinase 9 (CDK9) is a key transcriptional regulator and a lucrative target for cancer treatment. Targeting CDK9 can effectively confine the hyperactivity of androgen receptor and the constitutive expression of anti-apoptotic proteins; both being main causes of prostate cancer (PCa) development and progression. In castrate-resistant PCa, traditional therapies that only target androgen receptor (AR) have become obsolete due to reprograming in AR activity to make the cells independent of androgen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 132 publications
1
64
0
Order By: Relevance
“…CDK9, a member of the cdc2‐like serine/threonine kinase family, plays an important role in promoting cell proliferation and contribute to cancer . CDK9 is a crucial transcriptional regulator, and might serve as a new and better therapeutic opportunity for cancers treatment . Consistent with previous studies, we found that inhibition of CDK9 could suppress HCC cells proliferation, induce cell cycle at G0/G1 arrest, and apoptosis, which could be rescued by overexpression of CDK9.…”
Section: Discussionsupporting
confidence: 90%
“…CDK9, a member of the cdc2‐like serine/threonine kinase family, plays an important role in promoting cell proliferation and contribute to cancer . CDK9 is a crucial transcriptional regulator, and might serve as a new and better therapeutic opportunity for cancers treatment . Consistent with previous studies, we found that inhibition of CDK9 could suppress HCC cells proliferation, induce cell cycle at G0/G1 arrest, and apoptosis, which could be rescued by overexpression of CDK9.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study showed that inhibition of CDK2 suppressed PCa metastases by inactivating PI3K/Akt signaling (40). CDK5, CDK6, CDK7, and CDK9 can suppress CRPC through AR inactivation (41)(42)(43)(44). In addition, CDK inhibitors are currently being evaluated in clinical trials (45).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin-dependent kinase 9 (CDK9) is such a potential target for the treatment of CRC which plays a crucial role in the elongation step of global transcription process. Multiple studies using small molecule inhibitors and RNA interference have demonstrated that oncogenic transcription driven by CDK9 increases the survival and proliferation of cancer cells (Chen et al, 2005;Huang et al, 2014) and hence is continuously targeted for cancer treatment (Baker et al, 2016;Morales and Giordano, 2016;Rahaman et al, 2016). As CDK9 plays such a critical role in the transcription of a number of oncogenes (Krystof et al, 2012;Lam et al, 2001;Wang and Fischer, 2008), targeting CDK9 may provide a promising therapeutic strategy for the treatment of CRC.…”
Section: Introductionmentioning
confidence: 99%